Oracle SQL jumpstart with examples - Powell, Gavin; McCullough-Dieter, Carol (Amsterdam ; Boston : Elsevier Digital Press, 2005)
Developers and DBAs use Oracle SQL coding on a daily basis, whether for application development, finding problems, fine-tuning solutions to those problems, or other critical DBA tasks. Oracle SQL: Jumpstart with Examples is the fastest way to get started and to quickly locate answers to common (and uncommon) questions. It includes all the basic queries: filtering, sorting, operators, conditionals, pseudocolumns, single row functions, joins, grouping and summarizing, grouping functions, subqueries, composite queries, hierarchies, flashback queries, parallel queries, expressions and regular expressions, DML, datatypes (including collections), XML in Oracle, DDL for basic database objects such as tales, views and indexes, Oracle Partitioning, security, and finally PL/SQL. * Each of the hundreds of SQL code examples was tested on a working Oracle 10g database * Invaluable everyday tool that provides an absolute plethora of properly tested examples of Oracle SQL code * Authors have four decades of commercial experience between them as developers and database administrators.
Introduction to Oracle SQL -- New features of Oracle SQL -- Oracle database architecture -- The SELECT statement -- Filtering rows -- Sorting rows -- Operators, conditions, and pseudocolumns -- Using SQL*Plus -- Single-row functions -- Joining tables -- Grouping and summarizing data -- Subqueries -- Unusual query types -- Expressions -- Data manipulation language (DML) -- Datatypes and collections -- XML in Oracle -- Tables -- Views -- Constraints -- Indexes and clusters -- Sequences and synonyms -- Security -- Basic PL/SQL.
Includes bibliographical references and index.
Keywords: Oracle (Computer file); SQL (Computer program language).; Relational databases; Electronic books